The making of... a documentary in Cauca - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
In collaboration with Agronet, the Colombian Ministry of Agriculture and a professional camera team a documentary was filmed in the countryside of Cauca (Colombia). A farmer and an indigenous farmer explained us about their adaptations to climate smart agriculture, their changes in practices and the way modern technologies such as text messages with weather forecasts have been able to help them. Photocredits: Gian Betancourt (CIAT)